2013
DOI: 10.1111/jace.12301
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Plasticity in (GdxDy1−x)PO4 Fiber Coatings During Fiber Push Out

Abstract: The reduction in fiber push‐out stress by transformation plasticity in xenotime rare‐earth orthophosphate fiber–matrix interphases was demonstrated. Processing methods for transformable xenotime coatings were explored. For conversion to xenotime during processing, (GdxDy1−x)PO4 solid solutions had to be more Dy‐rich than those for pellets. Single‐crystal alumina fibers were coated with 10–20 μm of (Gd0.4Dy0.6)PO4 xenotime and incorporated into polycrystalline alumina matrices. Coated fiber push‐out stresses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
4
17
1
Order By: Relevance
“…12 In addition to the twin, numerous stacking faults, all along (100) planes, were observed in the deformed region (see supplementary material for addition TEM images). There was no evidence of a phase transformation in the deformed material; GdPO 4 is known to be stable in its monazite form under high pressures [2][3][4] and ambient conditions, and therefore, is unlikely to transform whereas some xenotime REPO 4 's can transform under pressure. 2,4,13 High shear stresses underneath the indentation likely promote twinning, but GdPO 4 is quite sensitive to the presence of shear stresses even in high-pressure diamond anvil cell experiments.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 90%
See 1 more Smart Citation
“…12 In addition to the twin, numerous stacking faults, all along (100) planes, were observed in the deformed region (see supplementary material for addition TEM images). There was no evidence of a phase transformation in the deformed material; GdPO 4 is known to be stable in its monazite form under high pressures [2][3][4] and ambient conditions, and therefore, is unlikely to transform whereas some xenotime REPO 4 's can transform under pressure. 2,4,13 High shear stresses underneath the indentation likely promote twinning, but GdPO 4 is quite sensitive to the presence of shear stresses even in high-pressure diamond anvil cell experiments.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 90%
“…1 As fiber coatings for CMCs, these materials readily absorb energy by plastically deforming via a variety of mechanisms including dislocation activity, fracture, and twinning, as well as phase transformations for some xenotime materials. 3,6,7 Previous studies in xenotime REPO 4 's and silicon have shown anomalous nanoindentation curve behavior -i.e., large elastic recovery in the unloading portion. 2,8 Hay et al completed nanoindentation studies highlighting this behavior in TbPO 4 , where a distinct variation (elbow) in the slope was observed upon unloading.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…Tb 0.5 Gd 0.5 PO 4 has a cation effective rare‐earth radius above that of TbPO 4 but it has a similar monazite transformation pressure of 10.5 GPa . In nonhydrostatic testing, the REPO 4 solid solution Gd 0.4 Dy 0.6 PO 4 was shown to have a lower fiber push‐out stress than DyPO 4 , which also coincides with the solid solution having a larger effective rare‐earth radius . But the hydrostatic transformation behavior and pressures of Gd x Dy (1− x ) PO 4 solid solutions and pure DyPO 4 have not been experimentally documented.…”
Section: Introductionmentioning
confidence: 85%
“…Certain REPO 4 fiber coatings with the xenotime structure (tetragonal, I 4 1 / amd ) have demonstrated a reduction in fiber push‐out stress compared to other xenotime‐ and monazite‐structured (monoclinic, P 2 1 / n ) REPO 4 fiber coatings. Specifically, Gd 0.4 Dy 0.6 PO 4 fiber coatings demonstrated significantly lower fiber push‐out stresses than DyPO 4 and LaPO 4 fiber coatings . Hay et al.…”
Section: Introductionmentioning
confidence: 97%
“…The zone axis for the Ni matrix is identified as [130] (Figure 9d), while the spots for the nano-precipitate are close to the simulation patterns of Ni 3 Si in the zone axis of [123] (Figure 9e). The simulation patterns for Ni and Ni 3 Si were performed using Singlecrystal™ software (CrystalMaker Software Limited, Oxfordshire, UK) [22,23]. Figure 9f presents the simulation of the combined NBD patterns for NiMo matrix and Ni 3 Si nano-particle in the zone axis of [130] and [132] respectively.…”
Section: Resultsmentioning
confidence: 99%